A review of the manufacture, mechanical properties and potential applications of auxetic foams. Issue 10 (19th April 2013) - Critchley, Richard; Corni, Ilaria; Wharton, Julian A.; Walsh, Frank C.; Wood, Robert J. K.; Stokes, Keith R.
<x xml:space="preserve">Abstract</x> Auxetics are a modern class of material fabricated by altering the material microstructure. Unlike conventional materials, auxetics exhibit a negative Poisson's ratio when subjected to tensile loading. These materials have gained popularity within the research community because of their enhanced properties, such as density, stiffness, fracture toughness and dampening. This paper provides a critical oversight of the auxetic field with particular emphasis to the auxetic foams, due to their low price, easy availability and desirable mechanical properties. Key areas discussed include the fabrication method, the effects played by different parameters (temperature, heating time, cell shape and size and volumetric compression ratio), microstructural models, mechanical properties and potential applications.